Air pollution and ST-elevation myocardial infarction: A case-crossover study of the Belgian STEMI registry 2009–2013. (15th November 2016) - Argacha, J.F.; Collart, P.; Wauters, A.; Kayaert, P.; Lochy, S.; Schoors, D.; Sonck, J.; de Vos, T.; Forton, M.; Brasseur, O.; Beauloye, C.; Gevaert, S.; et al.
Abstract: Background: Previous studies have shown that air pollution particulate matter (PM) is associated with an increased risk for myocardial infarction. The effects of air pollution on the risk of ST-elevation myocardial infarction (STEMI), in particular the role of gaseous air pollutants such as NO2 and O3 and the susceptibility of specific populations, are still under debate. Methods: All patients entered in the Belgian prospective STEMI registry between 2009 and 2013 were included. Based on a validated spatial interpolation model from the Belgian Environment Agency, a national index was used to address the background level of air pollution exposure of Belgian population. A time-stratified and temperature-matched case-crossover analysis of the risk of STEMI was performed. Results: A total of 11, 428 STEMI patients were included in the study. Each 10 μg/m 3 increase in PM10, PM2.5 and NO2 was associated with an increased odds ratio (ORs) of STEMI of 1.026 (CI95% : 1.005–1.048), 1.028 (CI95% : 1.003–1.054) and 1.051 (CI95% : 1.018–1.084), respectively. No effect of O3 was found. STEMI was associated with PM10 exposure in patients ≥ 75 y.o. (OR: 1.046, CI95% : 1.002–1.092) and with NO2 in patients ≤ 54 y.o. (OR: 1.071, CI95% : 1.010–1.136). No effect of air pollution on cardiac arrest or in-hospital STEMI mortality was found. Conclusion: PM2.5 and NO2 exposures incrementally increase the risk of STEMI. The risk related to PM appears to be greater in the elderly, while younger patients appear to be more susceptible to NO2 exposure.